Münşeat Mecmuaları ve Edebiyat Tarihimiz İçin Önemi - Haksever, Halil İbrahim (İlim Yayma Cemiyeti, 2000)
This work is concerned with the tinportance of "Münşeat Mecmuaları" (Collections of official letters) for the Literary history. These works has been written in the field of prose. The majority of the authors in this field are poet as well. Therefore except for their own literary value they are valuable sources in rendering information of history. In this context, this work interprets the works of Lamiî, Nergisî, Nabî and İbrahim Vehbî.
"Münşeat Mecmuaları" and Their Importance for the Literary History
Keywords: Divan Literature; Divan Prose; Münşeat; Literary History; Style